2021
DOI: 10.1007/s11071-021-06668-w
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear reduced-order model for vertical sloshing by employing neural networks

Abstract: The aim of this work is to provide a reduced-order model to describe the dissipative behavior of nonlinear vertical sloshing involving Rayleigh–Taylor instability by means of a feed forward neural network. A 1-degree-of-freedom system is taken into account as representative of fluid–structure interaction problem. Sloshing has been replaced by an equivalent mechanical model, namely a boxed-in bouncing ball with parameters suitably tuned with performed experiments. A large data set, consisting of a long simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…However, they suffer in being able to characterise well the dissipative capacity of the fluid at different values of amplitude and frequency as can be seen by comparing the energy maps provided in Refs. [10,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they suffer in being able to characterise well the dissipative capacity of the fluid at different values of amplitude and frequency as can be seen by comparing the energy maps provided in Refs. [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this work exploits the approach recently introduced in Ref. [16] for the generation of neural-network based ROM for vertical sloshing, by employing low-fidelity data and finally improved and experimentally validated for a sloshing beam in Ref. [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such experimental work is used, beside providing an understanding of the fundamental physical interactions, to create equivalent mechanical models (EMM) and reduced order models (ROM) with predictive capabilities. For vertical sloshing, such models involve bouncing balls interacting with vertically oscillating tanks, such as the models presented in [1,7]. De Courcy et al [8] proposed a bouncing-ball model coupled with an aeroelastic wing model that showed dissipative effects at multiple gust lengths.…”
Section: Introductionmentioning
confidence: 99%
“…An equivalent mechanical model consisting of a bouncing ball capable to reproduce the impact mechanisms, was proposed by Refs. [21,22]). These models provide fast prediction of sloshing forces, but since they are obtained by fitting the sloshing forces -or its induced damping -of the free response of a single degree of freedom system, they do not generally provide consistent results when working at frequencies different from those used in their identification.…”
Section: Introductionmentioning
confidence: 99%